Threonine requirements for rainbow trout (Oncorhynchus mykiss) and Atlantic salmon (Salmo salar) at the fry stage are similar - Bodin, Noelie; Mambrini, Muriel; Wauters, Jean-Baptiste; Abboudi, Tarik; Ooghe, Wilfried; Le Boulengé, Éric; Larondelle, Yvan; Rollin, Xavier (Aquaculture, 2008)
In order to compare the threonine (Thr) requirement and retention efficiency of rainbow trout and Atlantic salmon, we conducted a feeding experiment with 11 diets. For both species, we studied the effects of increasing dietary L-Thr: 5, 6.25, 7.5, 8.75, 10, 11.25, 12.5, 13.75, 15, 16.25, 21.75 g/kg dry matter (DM), on protein gain, Thr gain and Thr retention efficiency. All diets were isonitrogenous (40% DM) and isoenergetic (22.4 MJ gross energy/kg DM). To maintain the same nitrogen (N) level, the decrease of Thr in the diets was compensated by an increase of a mixture of dispensable amino acids. The rainbow trout and Atlantic salmon fry mean initial body weight was of 1.8 and 0.8 g, respectively, and they were fed for 24 and 36 days, respectively. The daily growth coefficient (% day(-1)) was much higher for rainbow trout fry (2.5% day 1) than for Atlantic salmon fry (1.1% day 1). For the Thr deficient diets (Thr levels <= 10 g/kg DM), feed efficiency and protein productive value were higher in trout than in salmon fry, and they were mainly related to differences in voluntary feed intake. The Thr requirements for optimal Thr accretion (+/- SE) determined by the broken-line model were equivalent among species: 10.58 +/- 0.56 and 10.66 +/- 0.36 g/kg DM or 2.6 +/- 0.1 and 2.7 +/- 0.1 g Thr/16 g N (P=0.4) for trout and salmon fly, respectively. At marginal dietary Thr concentrations (<= 10 g/kg DM), Thr accretion (mg/kg(0.75) per day) was a linear function of Thr intake (mg/kg(0.75) per day) for salmon and trout, but slopes were not significantly different (P=0.19). The slope of the single line estimation (r(2) =0.94) gave an estimate of the Thr retention efficiency above maintenance (SE) for both species (0.79 +/- 0.04). Additionally, the relationship between protein gain and Thr intake showed that trout and salmon required an intake of 70 and 62 mg of Thr, respectively, to deposit 1 g of body protein (P=0.21). Application of a simple factorial method to our data gave the same relative Thr requirement value ...